Application of hibah umra and ruqba in joint tenancy with right of survivorship: an analysis - Md.Habibur, Rahman; Puspa Liza, Ghazali; Md. Faruk, Abdullah; Noor Mohammad, Osmani (2018)
Umra and Ruqba are the two well known forms of donation of pre-Islamic period.Umra means donating something after making it contingent to the life of beneficiary. Once the beneficiary dies the donation will be expired and the donated object returns back to the donor. Ruqba means donating something subject to the survivorship of the other party. Thus, whoever survives upon demise of the other party, the donated object goes to his possession and consequently to his heirs. They are valid in Islamic law with the condition that the donated object should not be returned back to the donor.This paper strives to investigate the application of umra and ruqba donations into the joint tenancy with right of survivorship. Joint tenancy with right of survivorship refers to a legal arrangement whereby two or more parties jointly own a property with equal rights and responsibilities, provided that if one of them dies his portion in the property will be shifted to the possession of other survivors without any further legal action. The paper follows a qualitative method of analysis and investigation through relevant literatures.The paper posits that umra and ruqba donations are applicable to the joint tenancy arrangement, since they are basically the forms of hibah with the condition that whoever survives takes over the property. It concludes that joint tenancy arrangement with umra and ruqba secures the public wellbeing (maslahah) and implements the noble objectives of the shari’ah (maqasid al-shari’ah). Joint tenancy with umra and ruqba ensures that he or she does not lose the roof if another party dies.